2004
DOI: 10.1016/j.lungcan.2004.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous measurement of MMP9 and TIMP1 mRNA in human non small cell lung cancers by multiplex real time RT-PCR

Abstract: Summary Extracellular matrix (ECM) homeostasis is strictly maintained by a coordinated balance between the expression of matrix metalloproteinases (MMPs) and their specific inhibitors (TIMPs). Our study was focused on the simultaneous measurement of the expression profile of MMP9 mRNA and its principal inhibitor, TIMP-1, in 100 non small cell lung cancers (NSCLC) and in corresponding adjacent non malignant tissues. The measurement was performed with a multiplex quantitative RT-PCR assay based on TaqMan assay, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 25 publications
3
10
0
1
Order By: Relevance
“…Gouyer et al reported TiMP-1 expression to be an indicator of worse prognosis, but this was not related to TNM stage (23). In contrast, Simi et al reported that TiMP-1 expression was related not to patients survival, but rather to nodal spread and metastasis (24). Our results were in accord with those of Simi et al The fact that TIMP-2 was not related to prognosis and disease progression was also in agreement with previous reports (23,25).…”
Section: Discussionsupporting
confidence: 92%
“…Gouyer et al reported TiMP-1 expression to be an indicator of worse prognosis, but this was not related to TNM stage (23). In contrast, Simi et al reported that TiMP-1 expression was related not to patients survival, but rather to nodal spread and metastasis (24). Our results were in accord with those of Simi et al The fact that TIMP-2 was not related to prognosis and disease progression was also in agreement with previous reports (23,25).…”
Section: Discussionsupporting
confidence: 92%
“…Currently, there are more than 20 identified MMPs that can be categorized by substrate specificity. Despite the clinical significance of the pathogenetic impact of MMPs in human cancer, including PCa, only a few studies of MMPs are available in the literature, and those mainly analyze protein expression (18).…”
Section: Discussionmentioning
confidence: 99%
“…A number of past studies have successfully isolated RNA and protein from tumor samples, and profiled a limited number of MMPs 23-26. For example, protein was successfully extracted from thyroid tumors and relative MMP-1 and MMP-9 measurements were performed using a targeted enzyme linked immunoassay (ELISA) 35.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the absolute changes in MMP profiles with NSCLC which were observed in the present study, are likely the result of altered transcription pathways that are reflective of the underlying cancer process. Indeed, MMP expression profiles have been demonstrated to be directly associated with relevant process of tumor biology which include local growth and prognosis 1,5,7,11,23,25,26. The present study provides for a proof of concept that profiling of a large array of MMPs in NSCLC is possible, and could be expanded to reveal specific subsets of MMPs which hold both diagnostic and therapeutic relevance.…”
Section: Discussionmentioning
confidence: 99%